Spectral Approach to Derive the Representation Formulae for Solutions of the Wave Equation - Gusein Sh. Guseinov (Journal of Applied Mathematics)
Using spectral properties of the Laplace operator and some structural formula for rapidly decreasing functions of the Laplace operator, we offer a novel method to derive explicit formulae for solutions to the Cauchy problem for classical wave equation in arbitrary dimensions. Among them are the well-known d'Alembert, Poisson, and Kirchhoff representation formulae in low space dimensions.